2003
DOI: 10.1074/jbc.m305764200
|View full text |Cite
|
Sign up to set email alerts
|

Group I Metabotropic Glutamate Receptors Bind to Protein Phosphatase 1C

Abstract: The modulation of neurotransmitter receptors by kinases and phosphatases represents a key mechanism in controlling synaptic signal transduction. However, molecular determinants involved in the specific targeting and interactions of these enzymes are largely unknown. Here, we identified both catalytic ␥-isoforms of protein phosphatase 1C (PP1␥1 and PP1␥2) as binding partners of the group I metabotropic glutamate receptors type 1a, 5a, and 5b in yeast cells and pull-down assays, using recombinant and native prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…Therefore, 16 amino acids of mGluR7a and 23 amino acids of mGluR7b differ in their extreme C-terminal tails (31,32). Previous studies showed that PP1␥1 directly interacts with mGluR7b, but not mGluR7a, as determined using GST pulldown assays or yeast two-hybrid system interactions (33)(34)(35). This binding is mediated primarily by the N-terminal domain of PP1␥1 and the C-terminal region of mGluR7b (KSVTW; amino acids 911-915).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 16 amino acids of mGluR7a and 23 amino acids of mGluR7b differ in their extreme C-terminal tails (31,32). Previous studies showed that PP1␥1 directly interacts with mGluR7b, but not mGluR7a, as determined using GST pulldown assays or yeast two-hybrid system interactions (33)(34)(35). This binding is mediated primarily by the N-terminal domain of PP1␥1 and the C-terminal region of mGluR7b (KSVTW; amino acids 911-915).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases the negative signaling is due to a caspase-mediated cleavage of the receptor C-terminal domain (CTD) which either releases a pro-apoptotic C-terminal receptor fragment (Bordeaux et al, 2000;Llambi et al, 2001), or exposes a pro-apoptotic region that presumably remains bound to the cell membrane (Mehlen et al, 1998;Forcet et al, 2001;Thibert et al, 2003). While a specific cleavage of the mGlu1 CDT has not been described, it should be pointed out that a sequence analysis of the long CTD of the mGlu1a splice variant reveals six putative caspase cleavage sites, as well as multiple sequences that may potentially interact with a variety of intracellular proteins including: seven in absentia homolog-1A (Siah-1A) and calmodulin (Ishikawa et al, 1999;Kammermeier and Ikeda, 2001), G-proteincoupled receptor kinases (Dale et al, 2000), alpha-tubulin (Ciruela et al, 1999), tamalin/ cytohesin complex (Kitano et al, 2002), homer proteins (Brakeman et al, 1997;Tu et al, 1999), protein phosphatase 1C (Croci et al, 2003), protein kinase C, regulators of G-protein signaling (RGS) proteins, Src-family protein tyrosine kinase and arrestins (Valenti et al, 2002;Hermans and Challiss, 2001). Therefore, the mGlu1 CTD is well equipped to participate and interfere in various intracellular signaling processes.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of RNA and RT-PCR Total RNA was extracted from adult rat tissues, reverse transcribed and amplified as described (Croci et al 2003b) using primer pairs specific for the spectrin/actin binding domain (SAB) of 4.1B (sense nt1503-1523; antisense nt2313-2293) and the CTDs of 4.1B (sense nt3069-3087; antisense nt3424-3404), 41.G (sense nt2197-2217; antisense nt2646-2627), 4.1N (sense nt2133-2152; antisense nt2639-2618) and 4.1R (sense nt1959-1979; antisense nt2510-2491). Primers for the house keeping gene EF1a (sense nt1479-1497; antisense nt1770-1749) served as positive control.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%